Interim Election Protocol for Selecting Cluster Head to Mitigate Network Partitioning in NDN WSN - Singh, V. P; Ujjwal, R. L (International Journal of Computer Sciences and Engineering, 2018)
Immediately Advent of new technologies, such as content centric networking, IoT, smart grids, vehicular networks, machine to machine communication and smart application encourages the researchers to build autonomous, intelligent and selforganizing wireless sensor networks to preserve efficiency and maximize network lifetime. Clustering is considered as one of the most effective method for energy preservation and increasing network up time and it also come with challenges i.e.; selecting optimal nodes to be part of a cluster, fault tolerance and selecting cluster head for every cluster. To make selforganizing WSN, it is necessary to dynamically choose cluster head (CH) in case of accidental or natural death of CH also for preserving energy and mitigating network partitioning. This paper presents a short survey on various lifetime maximizing techniques, self-organization models and also proposed an protocol named IE protocol for selecting cluster head node initially also at the time of node failure to maximize network lifespan and palliate the network partitioning issue in WSN. We have evaluated performance of proposed protocol with previously proposed protocol like LEACH for WSN and NDN-WSN.